Detection of a waveguide in the basement of the northwestern shelf of the Black Sea according to the results of reinterpretation of the DSS materials of profiles 26 and 25 - Baranova, E. P.; Egorova, T.P.; Omelchenko, V. D. (S. Subbotin Institute of Geophysics of the NAS of Ukraine, 2011)
Results of reinterpretation of DSS materials along the profiles worked out within north-western shelf of the Black Sea near 45 years ago are given. Those are two seismic profiles crossed the shelf area: latitudinal DSS Profile 26 (Zmiyinyi Island - Tarkhankut Peninsula) and Profile 25, which crosses the western part of the Black Sea in sub-longitudinal direction. The wave field is character-ised by some special features in observed travel-time curves, which are indicative on the presence of wave guides here (the layers with decreased velocities). Velocity simulation produced by ray-tracing method along two profiles 26 and 25 indicated the presence in the basement and the upper part of consolidated crust of an inversion zone of complicated structure.The nature of a distinguished zone might by related to the occurrence of fault zones filled with rocks of increased jointing and porosity and the fluids, which may have under conditions of the north-western shelf hydrocarbon composition.